Single-course bleomycin, etoposide, and cisplatin (1xBEP) as adjuvant treatment in testicular nonseminoma clinical stage 1: outcome, safety, and risk factors for relapse in a population-based study. (March 2022) - Dieckmann, Klaus-Peter; Pokrivcak, Tomas; Geczi, Lajos; Niehaus, David; Dralle-Filiz, Inken; Matthies, Cord; Dienes, Tamas; Zschäbitz, Stefanie; Paffenholz, Pia; Gschliesser, Tanja; Pichler, Renate; Mego, Michal; et al.
Introduction: Clinical stage 1 (CS1) nonseminomatous (NS) germ cell tumors involve a 30% probability of relapse upon surveillance. Adjuvant chemotherapy with one course of bleomycin, etoposide, and cisplatin (1xBEP) can reduce this risk to <5%. However, 1xBEP results are based solely on five controlled trials from high-volume centers. We analyzed the outcome in a real-life population. Patients and Methods: In a multicentric international study, 423 NS CS1 patients receiving 1xBEP were retrospectively evaluated. Median follow-up was 37 (range, 6–89) months. Primary end points were relapse-free and overall survival evaluated after 5 years. We also looked at associations of relapse with clinico-pathological factors using stratified Kaplan–Meier methods and Cox regression models. Treatment modality and outcome of recurrences were analyzed descriptively. Results: The 5-year relapse-free survival rate was 96.2%. Thirteen patients (3.1%; 95% confidence interval, 1.65–5.04%) relapsed after a median time of 13 months, of which 10 were salvaged (77%). Relapses were mostly confined to retroperitoneal nodes. Three patients succumbed, two to disease progression and one to toxicity of chemotherapy. Pathological stage >pT2 was significantly associated with relapse rate. Conclusion: The relapse rate of 3.1% found in this population of NS CS1 patients treated with 1xBEP at the routine care level was not inferior to the median rate of 2.3% reported from a meta-analysis of controlled trials. Also, the cure rate of relapses of 77% is consistent with the previously reported rate of 80%. This study clearly shows that the 1xBEP regimen represents a safe treatment for NS CS1 patients.